2018
DOI: 10.1080/09585192.2018.1474938
|View full text |Cite
|
Sign up to set email alerts
|

HRM and innovation: the mediating role of market-sensing capability and the moderating role of national power distance

Abstract: This paper examines the mechanism through which human resource management (HRM) practices promote firms' innovation and how this relationship differs across cultures. Based on a dataset of 3,755 firms from 13 countries, this study finds that in most countries employee-oriented HRM practices that dedicate attention to employee needs and interests are positively related to firms' market-sensing capability, which is the capability to continuously learn about their markets. Market-sensing capability is in turn sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 112 publications
(140 reference statements)
3
20
0
10
Order By: Relevance
“…Research has shown that prominent national values in New Zealand include tolerance and support for equality (Sibley, Hoverd, and Duckitt 2011). Indeed, this is evidenced in low power distance (Lin et al 2018) and 'tall poppy syndrome' -a phenomenon that maintains that all individuals should be considered equal in all aspects of life (Kirkwood 2007, 366). Indeed, in line with these values, Prime Minister Jacinda Ardern announced that all government ministers (including the prime minister) and public service executives would take a 20% pay cut for six months, in solidarity with New Zealanders who had lost their jobs or taken significant pay cuts.…”
Section: Facebook Live Broadcast 29 March 2020mentioning
confidence: 99%
“…Research has shown that prominent national values in New Zealand include tolerance and support for equality (Sibley, Hoverd, and Duckitt 2011). Indeed, this is evidenced in low power distance (Lin et al 2018) and 'tall poppy syndrome' -a phenomenon that maintains that all individuals should be considered equal in all aspects of life (Kirkwood 2007, 366). Indeed, in line with these values, Prime Minister Jacinda Ardern announced that all government ministers (including the prime minister) and public service executives would take a 20% pay cut for six months, in solidarity with New Zealanders who had lost their jobs or taken significant pay cuts.…”
Section: Facebook Live Broadcast 29 March 2020mentioning
confidence: 99%
“…According to Lin, Sanders, Sun, Shipton, and Mooi (Lin et al, 2020) capabilities and abilities majorly be defined as critical collections of abilities and combined learning process, mainly conducted through firm marketing practices that secure significant management of operational activities (Bouguerra et al, 2017). One capability is demonstrated to be difficult in creating successful and profitable firms; the market sensing capability (MSC), which is typically an ability or property of the company to be interpreted of modification in its internal market and also to evaluate significantly responses to its marketing steps (Brown et al, 2019).…”
Section: The Relationship Between Market Sensing Capability (Msc) And...mentioning
confidence: 99%
“…These HR practices are very much goal oriented and are very exclusive and significant, and are likely to improve performance of the organization (Boon, Hartog, & Lepak, 2019;Gabriel, Cheshin, Moranc, & van Kleef, 2015), by associating HR with quality assurance can be influential in setting high performance parameters. Literature associated with HR and its management advocates that these activities make meaningful assistance towards organization creative sense (Fay, Shipton, West, and Patterson, (2015); Lin, Sanders, Jian-Min, Shipton & Mooi, 2018). One of the important HR attributes is training session for employees, which allow them to build their capabilities, improve knowledge and refine their skills; which ultimately translate into basis for innovative concepts, operations and practices for organization.…”
Section: Literature Reviewmentioning
confidence: 99%